Effects of Weed Control Practices on Plant Diversity in a Homogenous Olive-Dominated Landscape (South-East of Italy) - Massimo Terzi; Emanuele Barca; Eugenio Cazzato; Francesco Saverio D’Amico; Cesare Lasorella; Mariano Fracchiolla (Plants, 2021)
Olive groves represent an important economic, agro-ecological, and cultural resource in the Mediterranean Basin. Weed management plays a fundamental role in their sustainable management. The aim of this work was to characterize and assess the plant diversity associated with different weed control practices, in a homogeneous olive-dominated landscape in the South-East of Italy. Sixty-five vegetation plots were sampled in orchards treated with different weed control practices: mowing, tillage, and use of chemical herbicides. The multi-response permutation procedure was used to test the hypothesis of no difference among the treatments. The relationships between plots were visualized by means of non-metric multidimensional scaling ordination. A generalized linear mixed model was used to analyze the relationships between weed control practices and life forms, chorotypes, and diversity indexes. The results showed that the three weed control practices determined slightly different plant communities. Chemically weeded orchards showed an impoverished floristic composition and the lowest diversity, whereas mowing and tillage yielded similar values. These latter two treatments differed for the percentages of hemicryptophytes and therophytes. Moreover, different from other studies, we did not find plant species of particular concern for biodiversity conservation. We hypothesize that this result is due to the monotonous structure of the agro-landscape we investigated, where natural elements are almost lacking. From this point of view, a correct management of agro-districts should consider both the agronomic practices at the level of the individual olive groves and the structure of the agro-landscape.